Peran Komunikasi Interkultural dalam Penguatan Moderasi Beragama Pada Masyarakat Kota Medan (Analisis FKUB di Medan) - Pratama, Teguh Agum; Harahap, Nursapia (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Indonesia Banda Aceh, 2024)
This article focuses on the analysis of strengthening religious moderation in the people of Medan City which is promoted by the Medan City FKUB using an intercultural communication perspective. This is because the problem of intolerance is the root of social problems that can divide society, especially in Medan, which is a multicultural city. The urgency of this study rests on how intercultural communication is able to initiate attitudes of tasamuh and unity regarding differences through the support of contact communication between groups. Religious harmony forums have a role in creating a forum for culturally and religiously heterogeneous communities. This study adopts a qualitative method with a phenomenological approach. The data collection techniques used in this article are interviews, observation and documentation supported by primary and secondary data. This article uses thematic analysis techniques to better understand the observed phenomenon. The results of this study emphasize the importance of intercultural communication and intergroup contact in supporting religious moderation, which is the key to creating a tolerant, just and balanced society. Intercultural communication is effective in promoting inter-religious dialogue, religious discourse, and religious seminars. In order to overcome bad prejudice and strengthen tolerance. This approach is also vital in conveying information and the concept of religious moderation. Despite technical and semantic challenges, the implementation of intercultural communication can make a significant contribution to religious discussions and unity. FKUB in Medan City has demonstrated success in implementing this approach, creating a harmonious social space and respecting differences as gifts, by promoting collective support for humanitarian principles.